Preparation of Natural Ouw Clay-Chitosan Composite and Its Application as Lead and Cadmium Metal Adsorbent - Bijang, Catherina M.; Tanasale, M.F.J.D.P.; Kelrey, Adhi G.; Mansur, Inda Ulfa; Azis, Thamrin (Indonesian Journal of Chemical Research, 2021)
This study aims to obtain the optimum ratio of Ouw Natural Clay (LAO):Chitosan in the manufacture of chitosan-LAO composites. The composite will be used as an adsorbent for heavy metals Lead (Pb) and Cadmium (Cd). LAO-Chitosan composites were made with the ratio of LAO:Chitosan = 1.25:1, 2.5:1, 5:1. XRD and SEM were carried out for each composite. The performance as a Cd metal adsorbent was determined by calculating the adsorption capacity. Composites with a ratio of 1.25:1 have the best adsorption capacity. The performance as adsorbent for Cd metal was determined by calculating the absorbed Cd concentration. Maximum results are achieved by composites with a ratio of 5:1.